Avaliação radiográfica de lesões periapicais e análise de alterações metabólicas em ratos pré-diabéticos - Zago, Natália Brezolin (2014)
Introduction: The aim of this research work was to compare the radiographic periapical lesions in teeth of diabetic and nondiabetic rats and do an analysis of the metabolic differences of these animals. Methods: 16 male Wistar rats divided into two groups: Group I (n = 8) group rats received chow and filtered water; Group II (n = 8) rats received hypercaloric diet during a 10-week period. After 6 weeks the start of administration of the diet, periapical lesions were induced in the first molars with coronary opening, pulp removel and root canal exposure to the oral environment for a period of 28 days. After this period, the animals were euthanized, blood was made collection was perfomed, followed by liver and abdominal fat removal and, subsequently, the mandible was removed to perform radiographic analysis. Data were subjected to statistical analysis with a significance level set at α=0:05. The difference between groups was analyzed by Student's t-test. Results: There was no statistical difference between diabetic and nondiabetic rats (P>0.05) in radiographic analysis. In blood test statistical difference between diabetic and non-diabetic mice (P<0.05) in the level of catalase cosumo weekly weighed and feed was observed. Conclusion: The induction of diabetes with a high calorie diet for a period of 10 weeks did not show differences in the sizes of periapical lesions evaluated in these animals. In addition, the metabolic differences in these animals were not observed, except in the level of catalase, weekly weighing and feed intake.